Caffeine and menopausal symptoms: what is the association?. Issue 2 (February 2015) - Faubion, Stephanie S.; Sood, Richa; Thielen, Jacqueline M.; Shuster, Lynne T.
Abstract: Objective: We assessed the association between caffeine intake and menopausal symptom bother, particularly vasomotor symptoms. Methods: A cross-sectional survey was conducted using the Menopause Health Questionnaire, which is a comprehensive survey of menopause-related health information. Questionnaires were completed by 2, 507 consecutive women who presented with menopausal concerns at the Women's Health Clinic at Mayo Clinic (Rochester, MN) between July 25, 2005 and July 25, 2011. Data from 1, 806 women who met all inclusion criteria were analyzed. Menopausal symptom ratings were compared between women who used caffeine and women who did not use caffeine using two-sample t test and analysis of covariance, with smoking and menopause status included as covariates. In all cases, two-tailed P < 0.05 was considered statistically significant. Results: Caffeine use was positively associated with mean (SD) vasomotor symptom scores (2.30 [0.91] vs 2.15 [0.94], P = 0.011). This finding remained significant after adjustment for menopause status and cigarette smoking ( P = 0.027). Conclusions: Caffeine use is associated with greater vasomotor symptom bother in postmenopausal women.